Essentials of WISC-V assessment - Flanagan, Dawn P.; Alfonso, Vincent C. (Essentials of psychological assessment, 2017)
"The comprehensive reference for informative WISC-V assessment Essentials of WISC-V Assessmentprovides step-by-step guidance for administering, scoring, and interpreting the Wechsler Intelligence Scale for Children (WISC-V). Packed with practical tips for more accurate assessment, this informative guide includes numerous case studies that illustrate a range of real-world issues. Special attention is devoted to the assessment of individuals who have significant learning difficulties, such as learning disabilities, and who speak English as a second language. The WISC-V is a valuable assessment tool, but it must be administered and scored appropriately to gain meaning from score interpretation. This book gives you an in-depth understanding of the WISC-V assessment and interpretive process to assist practitioners in: Conducting efficient and informative WISC-V assessments Utilizing WISC-V in cross-battery and neuropsychological assessment Applying WISC-V in the identification of specific learning disabilities Utilizing WISC-V in nondiscriminatory assessment of English language learners Writing theory-based WISC-V reports Linking WISC-V findings to interventions based on individual performance As the world's most widely-used intelligence test for children, the WISC-V is useful in diagnosing intellectual disabilities and specific learning disabilities, as well as in identifying giftedness. In this volume, sample reports demonstrate how WISC-V assessment results may be linked to interventions, accommodations, modifications, and compensatory strategies that facilitate positive outcomes for children. Essentials of WISC-V Assessment is the all-in-one practical resource for both students and practitioners. The book can be used on its own or with companion software (purchased separately) that provides a user-friendly tool for producing psychometrically and theoretically defensible interpretations of WISC-V performance, and may be used to develop interventions based on each child's strengths and weaknesses."--Provided by publisher.